2007
DOI: 10.1007/s10620-007-0111-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Portal Hypertension in the Small Bowel: An Endoscopic Approach

Abstract: Background and aim The effects of portal hypertension in the small bowel are largely unknown. The aim of the study was to prospectively assess portal hypertension manifestations in the small bowel. Methods We compared, by performing enteroscopy with capsule endoscopy, the endoscopic findings of 36 patients with portal hypertension, 25 cirrhotic and 11 non-cirrhotic, with 30 controls. Results Varices, defined as distended, tortuous, or saccular veins, and areas of mucosa with a reticulate pattern were significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 31 publications
7
44
1
1
Order By: Relevance
“…The edema of the intestinal lumen had the typical reticulate pattern reported by Figueiredo et al [9] in patients with liver cirrhosis (fig. 2, 3).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The edema of the intestinal lumen had the typical reticulate pattern reported by Figueiredo et al [9] in patients with liver cirrhosis (fig. 2, 3).…”
Section: Discussionsupporting
confidence: 63%
“…They detected villous abnormalities in 14 of these patients, including edema (73%), atrophy (40%) and reddening of the villi (47%), as well as vascular lesions such as angiodysplasia-like abnormalities (67%) and dilated/proliferated vessels (93%). Figueiredo et al [9] reported a significant amount of varices (28%) and areas of mucosa with a reticulate pattern (61%) in 36 patients with portal hypertension examined by capsule endoscopy. Ganc et al [10] examined small intestinal lesions in 9 patients with portal hypertension of schistosomal origin using capsule endoscopy.…”
Section: Introductionmentioning
confidence: 99%
“…The reported prevalence of PHG varies greatly from 20% to 75% in patients with portal hypertension (Table 1) [3,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] , and varies greatly from about 35% to 80% in patients with cirrhosis (Table 2) [21, . For example, in a study of 373 cirrhotic patients, 299 (80.2%) had PHG [34] .…”
Section: Epidemiologymentioning
confidence: 99%
“…Itha et al [11] EHPVO in children 163 (12%) Not reported Not reported Rana et al [12] Portal hypertension 41 27 (66%) 19 (46%) 8 (20%) El-Rifai et al [13] Portal hypertension 24 14 (58%) 10 (42%) -moderate 4 (16%) Sogaard et al [14] Portal vein thrombosis 67 28 (42%) Not reported Not reported Figueiredo et al [15] Portal hypertension; cirrhosis 36 27 (75%) 5 (46%) Erden et al [16] Portal hypertension 57 15 (26.3%) Not reported Not reported Duché et al [17] Children, portal hypertension with biliary atresia 125 …”
Section: Not Reported Not Reportedmentioning
confidence: 99%
“…With regard to PHE, the few studies in the literature report a prevalence between 15% and 96.8% in patients with cirrhosis and PHT. However, the number of patients with PHE is probably much higher, with figures between 40% and 96.8% in some series (8)(9)(10)(11)(12)(13)(14)(15). As in the case of PHG, these discrepancies are probably due to differences in the criteria used for patient selection and endoscopic interpretations.…”
Section: Introductionmentioning
confidence: 98%